Cancer as a metabolic disease : on the origin, management, and prevention of cancer - Seyfried, Thomas N., 1946- (Hoboken : John Wiley & Sons, 2012)
The book addresses controversies related to the origins of cancer and provides solutions to cancer management and prevention. It expands upon Otto Warburg's well-known theory that all cancer is a disease of energy metabolism. However, Warburg did not link his theory to the "hallmarks of cancer" and thus his theory was discredited. This book aims to provide evidence, through case studies, that cancer is primarily a metabolic disease requiring metabolic solutions for its management and prevention.
10. Respiratory Insufficiency, the Retrograde Response, and the Origin of Cancer.
Includes bibliographical references and index.
Print version record.
Keywords: Cancer -- Prevention; Neoplasms -- diet therapy; Neoplasms -- metabolism; Energy Metabolism; Ketogenic Diet; Mitochondria -- metabolism; Medicine; MEDICAL -- Oncology; Cancer -- Prevention; Electronic books